BRAFi/MEKi in patients with metastatic melanoma: predictive factors of complete response. (10th September 2018) - Ribero, Simone; Malavenda, Ottavia; Fava, Paolo; Astrua, Chiara; Marra, Elena; Osella-Abate, Simona; Sanlorenzo, Martina; Caliendo, Virginia; Fierro, Maria Teresa; Quaglino, Pietro
Aim: A survival benefit was demonstrated by dabrafenib + trametinib for metastatic BRAF -mutated melanoma patients. Best response is a strong prognostic marker for survival.Patients & methods: The specific features associated with complete response (CR) were evaluated.Results: A total of 15/66 patients achieved CR. Median size of lesions was 3 cm (range: 0.5–10). Using that value as cut-off, the CR rate was 39.3% in patients with smaller lesions and 10.5% in patients with bigger size (p = 0.006). The clinical features associated with CR were the number of metastatic sites and the largest diameter of the biggest metastatic site.Conclusion: The number of the metastases and the diameter of the largest metastatic site are associated with a higher CR rate.